Modeling localized corrosion in biofuel storage tanks - Hossein Moradi; Gabriele Grifò; Maria Francesca Milazzo; Edoardo Proverbio; Giancarlo Consolo (Mathematical Biosciences and Engineering)
This work aims to model the influence of biofuels on localized 'pitting' corrosion that occurs at the bottom of atmospheric storage tanks. To achieve this purpose, an electro-chemical phase-field model is proposed to include the extra chemical reaction due to the presence of organic acids in an electrolyte solution. The resulting set of nonlinear coupled partial differential equations is numerically integrated by means of finite element methods with a twofold aim: tracking the evolution of the metal/electrolyte interface and predicting the corrosion rates observed when either single or multiple interacting pits are formed in the bottom of a carbon steel tank. The results obtained in the case of single pit, which exhibited a good quantitative agreement with recent experimental data, can be summarized as follows: the presence of organic acids led to higher corrosion rates in comparison with conventional fuels; the corrosion rate is a two-stage process; the dependence of the pit depth as a function of time; and the solid potential, which can be successfully described via a double power law. For multiple interacting pits, the larger corrosivity associated to biofuels was further amplified and the long-time behavior of pit growth gave rise to a 'band' behavior, with the major role being played by the number of pits rather than the initial spacings among them. Thus, the proposed model can be employed as a sophisticated tool to predict and quantify the real hazards associated with the release of pollutants in the environment, as well as to optimize the maintenance strategies based on an improved risk-based inspection planning.